Achieving carbon neutrality in China: Spectral clustering analysis of plant diversity - Li, Ping; Li, Rita Yi Man; Chen, Hong; Cao, Yong; Kaabar, Mohammed K. A. (Frontiers in Environmental Science, 2022)
Plants have long history and diverse species. They play a critical role in the ecological chain, human production and life. With a vast territory, China has rich plant species and complex geographical regions. Thus, research on the distribution of plant diversity in China is significant for utilising, developing, and protecting biological resources. This study obtained the plant diversity distribution data in China and then analysed it via spectral clustering. It was found that the Hengduan Mountains were the main route for Chinese plants to migrate from the west to the east, which might be closely related to the Himalayan orogeny. The Himalayan orogeny promotes the formation of the Qinghai–Tibet Plateau as a vital factor in the biodiversity formation in China. Thus, this study provides a basis for China’s conservation and study and enhances our understanding of plant biodiversity. As plant biodiversity increases soil organic carbon storage, this study provides insights into carbon neutrality practitioners and researchers.